Early Machine Learning Research in Ljubljana (Informatica, 2018)
We describe early machine learning research in Ljubljana, motivated by medical diagnostic problems, in the areas of building decision trees with Assistant, the development of Naïve and Semi-Naïve Bayesian classifier and its explanations of individual predictions, and the development of ReliefF and RReliefF algorithms for non-myopic evaluation of attributes in classification and regression, respectively.